DAMPAK LIKUIDITAS, RISIKO BISNIS, UKURAN PERUSAHAAN, DAN DIVIDEN TERHADAP STUKTUR MODAL PERUSAHAAN JASA NON KEUANGAN - Ho, Juan; Lukman, Hendro; Simina, Juni (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This research has a purpose to find empirical evidence about whether or not the influence of liquidity, business risk, firm size, and dividend on capital structure. This study used 78 data sample from non-banking service company listed on the Indonesian Stock Exchange 2015 – 2020. Sample was selected by purposive sampling. Testing in this study used multiple regression analysis techniques by using Statistical Package for Social Science (SPSS 28.0). The end result of this study suggest that liquidity and firm size influence the capital structure. While business risk and dividend does not influence the capital structure. The implication, company need to pay awareness to variables such as liquidity and firm size when the company want to make a decision about capital structure.